Half‐Sandwich Ruthenium(II) Biotin Conjugates as Biological Vectors to Cancer Cells. Issue 13 (12th February 2015) - Babak, Maria V.; Plażuk, Damian; Meier, Samuel M.; Arabshahi, Homayon John; Reynisson, Jóhannes; Rychlik, Błażej; Błauż, Andrzej; Szulc, Katarzyna; Hanif, Muhammad; Strobl, Sebastian; Roller, Alexander; Keppler, Bernhard K.; et al.
Abstract Ruthenium(II)–arene complexes with biotin‐containing ligands were prepared so that a novel drug delivery system based on tumor‐specific vitamin‐receptor mediated endocytosis could be developed. The complexes were characterized by spectroscopic methods and their in vitro anticancer activity in cancer cell lines with various levels of major biotin receptor (COLO205, HCT116 and SW620 cells) was tested in comparison with the ligands. In all cases, coordination of ruthenium resulted in significantly enhanced cytotoxicity. The affinity of RuII–biotin complexes to avidin was investigated and was lower than that of unmodified biotin. Hill coefficients in the range 2.012–2.851 suggest strong positive cooperation between the complexes and avidin. To estimate the likelihood of binding to the biotin receptor/transporter, docking studies with avidin and streptavidin were conducted. These explain, to some extent, the in vitro anticancer activity results and support the conclusion that these novel half‐sandwich ruthenium(II)–biotin conjugates may act as biological vectors to cancer cells, although no clear relationship between the cellular Ru content, the cytotoxicity, and the presence of the biotin moiety was observed.